Tertiary Syphilis Involving the Larynx: A Rare Case Report. Issue 5 (September 2021) - Thakkar, Bhushan; Carlisle, Wesley D.; Redfield, Samantha; Meram, Andrew T.
Abstract : Abstract: Syphilis is one of the most common sexually transmitted diseases. In recent years, a resurgence of syphilis has been described in the literature, with a 71.4% increase in documented cases in the United States from 2014 to 2018. Tertiary syphilis remains rare in developed countries. We report a case of tertiary laryngeal syphilis in a middle-aged man presenting with cervical lymphadenopathy and an oropharyngeal mass with clinical features suggestive of malignancy. Precise pathologic examination with laboratory testing revealed the final diagnosis. We review the imaging and pathologic findings to emphasize the importance of taking syphilis into consideration in the differential diagnosis of oropharyngeal masses. Abstract : There has been a resurgence of syphilis, and the diagnosis should be considered in the differential diagnosis of masses in the head and neck region.